IMPLEMENTASI SUPERVISI DIREKTIF DALAM PENINGKATAN KUALITAS PENGAJARAN INKLUSI DI SEKOLAH DASAR NEGERI GADINGKASRI - Natasya, Nindiya Zalwa (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2025)
This study aims to analyze the implementation of directive supervision in improving the quality of inclusive teaching at SDN Gadingkasri. Directive supervision is considered appropriate because it emphasizes clear guidance, direct feedback, and intensive assistance for teachers an essential aspect in inclusive learning contexts where teachers act as the primary source of instruction. This research employs a qualitative approach, utilizing direct classroom observations and in-depth interviews with classroom teachers, special education support teachers, and the principal. The observations focus on how directive supervision is carried out, the types of guidance provided, and the changes observed in inclusive teaching practices. The findings are expected to offer empirical insights into the effectiveness of directive supervision in helping teachers address diverse student needs, enhance learning interactions, and strengthen pedagogical competence in an inclusive school environment. Moreover, the results are intended to contribute to the development of more adaptive and sustainable supervision strategies in primary schools.